1999
DOI: 10.1093/jmedent/36.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofEscherichia coliO157:H7 fromMusca domestica(Diptera: Muscidae) at a Cattle Farm in Japan

Abstract: Enterohemorrhagic Escherichia coli (EHEC) O157:H7 was isolated for the first time from Musca domestica L. A total of 310 fly samples was collected from 4 different farms in Obihiro-City, Hokkaido, in the summer and autumn of 1997;5 samples carried E. coli serotype O157:H7. Using ELISA and Vero cell cytotoxicity assay, 3 isolates from 1 cattle farm produced both active Shiga-toxin type 1 (Stx1) and 2 (Stx2). These isolates also carried hemolysin and eaeA genes and harbored the 90-kb virulence plasmid of EHEC O1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 21 publications
1
65
0
3
Order By: Relevance
“…24 Thirty flies were removed from each cage by aspirator 26 on days 3, 5, 7, 9, and 11 after they emerged. They were killed by exposure to low temperature (Ϫ20ЊC), 21 placed into a plastic tube with 50 ml of eluting fluid, 27 and vortexed. The eluant with the flies was filtered onto the surface of a 25-mm-diameter cellulose acetate membrane (CAM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Thirty flies were removed from each cage by aspirator 26 on days 3, 5, 7, 9, and 11 after they emerged. They were killed by exposure to low temperature (Ϫ20ЊC), 21 placed into a plastic tube with 50 ml of eluting fluid, 27 and vortexed. The eluant with the flies was filtered onto the surface of a 25-mm-diameter cellulose acetate membrane (CAM).…”
Section: Methodsmentioning
confidence: 99%
“…15 Cattle manure is recognized source of C. parvum oocysts, 16,17 and is also a favorite breeding place, food source, and descending site of house flies. [18][19][20] Although house flies come into direct contact with manure, and it has been demonstrated that small particles readily adhere to the exterior surfaces of the fly, 21,22 the role of house flies as the transport hosts for C. parvum oocysts has not been elucidated. The purpose of the present study was to determine if house flies can serve as transport hosts for infectious C. parvum oocysts.…”
mentioning
confidence: 99%
“…6 Refuse and promiscuous-landing synanthropic filth flies are recognized transport hosts for a variety of parasites of public health and veterinary importance. [7][8][9][10][11][12][13][14] These include the coccidian parasites Sarcocystis spp., Toxoplasma gondii, Isospora spp., and Eimeria tenella. 7,[10][11][12]14 Cryptosporidium parvum infections are particularly prevalent in pre-weaned cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental infection with Stx-negative O157 and bac-teriophage to the sheep: Approximately 10 9 cells of Stx non-producing O157:H7 (Stx-negative O157) originating from house fly [9], which was grown in BHI at 37°C for 16 hr with shaking, were orally inoculated to the sheep after the above experiments to isolate STEC. Then, five pieces of fresh feces were weekly collected for 20 weeks and directly plated on DHL and Sorbitol MacConkey (SMC; Eiken Co., Ltd.) agar plates, and O157 colonies were counted as described above.…”
Section: Sheepmentioning
confidence: 99%